Some child cost estimates for South Africa - Sienaert, A (CSAE (University of Oxford), 2008)
The heterogeneous demographic composition of South African households means that the way that household income or expenditure is converted into an individual-level welfare measure is likely to matter. This paper examines the monetary and time costs of the most common economic dependents in households: children. The monetary costs of children are estimated at about half those of an adult. Time costs are substantial, and borne almost exclusively by women. Estimates that incorporate time costs suggests that children's "full costs" are about twice monetary costs alone; with household resources fixed, the average, combined expenditure and time impact of children is very similar to adding an equivalent number of adults.